Diversity and succession of microbial communities on typical microplastics in Xincun Bay, a long-term mariculture tropical lagoon - Shi Yunfeng; Wang Shuai; Wang Hui; Li Zhaoyang; Cai Jiali; Han Qiuying; Zhao Muqiu (Oceanological and Hydrobiological Studies)
In this study, three polymer types of microplastics (MPs), polyethylene (PE), polystyrene (PS) and polypropylene (PP), were exposed for 60 days in Xincun Bay (Hainan, China), a long-term mariculture tropical lagoon. High-throughput sequencing and scanning electron microscopy (SEM) were used to investigate the succession of microbial community structure and function on MPs after 10, 30, and 60 days of exposure, respectively. The results showed that diversity indices for bacteria from MPs were higher than those for bacteria from seawater. Significant differences were observed in community structure and metabolic function between MPs and seawater. The microbial network structure on MPs was more complex and dispersed than that in seawater. No significant differences in bacterial community structure and metabolic function were observed among different types of MPs. The biofilm on PS was the thickest, and the network structure on PP was the most complex one. With increasing exposure time, the biofilm attached to the surface of MPs became thicker and microbial composition showed some differences. The analysis of potential degradation bacteria and pathogens with abundance above 0.01% showed that the abundance of several potential plastic biodegraders on MPs was higher than that in seawater, while no potential pathogen was found enriched on MPs.